Pendampingan Pengurusan Dokumen Kekayaan Intelektual di CV. Herba Sedunia Ponorogo - Maretha Berlianantiya; Nizam zakka arrizal (CV. Agrapana Media, 2025)
This community service activity aims to enhance the understanding, legal awareness, and administrative capabilities of business actors in managing intellectual property documents and business legality. The partner in this program is CV. Herba Sedunia Ponorogo, a company engaged in the production of traditional herbal medicines and beverages, which previously lacked complete legal documentation such as risk-based business permits, halal certification, and trademark registration. The implementation method consisted of three stages: needs assessment and partner analysis, legal counseling and technical assistance, and evaluation of the program outcomes. A participatory approach was applied to ensure that the partner was actively involved in each stage of the legal documentation process and could understand the practical mechanisms directly. The counseling materials covered the basic concepts of Intellectual Property Rights (IPR), the importance of trademark protection, the online registration procedure through the DJKI system, and business licensing through the Online Single Submission (OSS) platform. The results of the activity showed a significant increase in the partner’s knowledge and skills. Based on the pre-test and post-test results, the participants’ average score increased from 50 to 88, indicating the success of the program in strengthening legal literacy and administrative awareness among business actors. Furthermore, the partner successfully prepared trademark registration documents, obtained a risk-based business license, and secured halal certification for its herbal products. This activity has proven effective in fostering a culture of legal awareness among MSME entrepreneurs and serves as a model for local economic empowerment based on intellectual property protection and product innovation.